Development of sofosbuvir for the treatment of hepatitis C virus infection. Issue 1 (31st July 2015) - Lawitz, Eric; Jacobson, Ira M.; Nelson, David R.; Zeuzem, Stefan; Sulkowski, Mark S.; Esteban, Rafael; Brainard, Diana; McNally, John; Symonds, William T.; McHutchison, John G.; Dieterich, Douglas; Gane, Edward
Abstract : The nucleotide analog NS5B polymerase inhibitor sofosbuvir was approved by the U.S. Food and Drug Administration (FDA) in December 2013 for the treatment of chronic hepatitis C virus (HCV) infection in combination with ribavirin or peginterferon and ribavirin. Sofosbuvir was developed to meet an urgent medical need for shorter, safer, simplified, more effective HCV treatment regimens and to reduce or eliminate the need for peginterferon. New treatment regimens were especially required for patient populations with limited treatment options, including patients who had failed prior HCV therapy, those with compensated and decompensated cirrhosis, and those who were either intolerant of or had contraindications to interferon. Sofosbuvir plus ribavirin for patients with genotype 2 or 3 HCV infection was the first approved all‐oral treatment option. Sofosbuvir is also the backbone of the first regimen available for patients awaiting liver transplantation to prevent HCV recurrence, as well as the first oral interferon‐free regimen for patients coinfected with HCV and HIV. This paper describes the development of sofosbuvir up to its original FDA approval.